Enriched silicon and Bacillus subtilis on Fusarium wilt disease control and their effects on growth and physio-biochemical changes of banana - Zakaria, Md Aiman Takrim (2022)
Musa acuminata (cv. Berangan) belonging to the Musaceae family are sensitive to the biotic stress condition affecting growth performance and physio-biochemical changes. Fusarium wilt disease caused by Fusarium oxysporum f.sp. cubense (FOC) is considered the most limiting factor in the vegetative and reproductive growth of the banana. The study’s general objective was to investigate the potential effect of enriched silicon (Si) compounds, antagonistic bacteria and systemic fungicide on plant growth and physio-biochemical changes in controlling FOC. The treatments in the main plot for each greenhouse experiment were divided into healthy plants without FOC inoculation and diseased plants. For the treatments in the sub-plot, the soil planting media in Experiment 1A were drenched with a different nutrient formulation of enriched Si compound [T0 served as control, T1: 13% SiO2 and 20% K2O, T2: 26.6% SiO2 and 13.4% K2O and T3: 36.2% SiO2 and 17% Na2O]. Experiment 1B, only the best selected of enriched Si compounds applied at different application frequency [0, 7, 15, 30 days of interval (DI)]. Experiment 2A, the sub-plot treatments consisted of different species of antagonistic bacteria: 0B (without Bacillus application served as control), BS (Bacillus subtilis) and BT (Bacillus thuringiensis). For Experiment 2B, banana plants were treated with different application volume of selected enriched Si compound [0, 20, 40, 60 mL] before integrating with the best selected antagonistic bacteria Field assessment in the Experiment 3 was conducted in a Fusarium infected area and banana plants were subjected to treatment: Control (without any treatments), CBZ (Carbendazim), T3+BS (36.2% SiO2 + 17% Na2O + Bacillus subtilis) and CBZ+T3+BS (CBZ + 36.2% SiO2 + 17% Na2O + Bacillus subtilis). Results in the Experiment 1A showed that diseased banana plant significantly reduced plant height, pseudo-stem diameter, total leaf area (TLA) and total chlorophyll content (Chla+b) by 38.39%, 88.23%, 19.74% and 30.43%, respectively as compared to healthy plants. In the Experiment 1B, the best growth performance was observed when infected banana clones applied with T3 at 15DI, significantly reduced disease incidence by 58.2% and proline content by 44.28%. Results in Experiment 2A showed the amount of TPC started to increase from 81.52 to 175.15 μg/g FW when the proline content of the banana clones started to increase from 23.79 to 51.34 μmol/g FW under different soil and plant health conditions. In Experiment 2B, the results showed exogenous application of enriched Si compounds with BS at 15DI on the soil and roots of banana clones significantly increased the electrolyte leakage (EL) by 2.94% (40 mL) and 11.27% (60 mL), but application 20 mL significantly reduced EL by 8.75% in relative to the control (0mL) by 53.67%. Based on field assessment in the Experiment 3, banana clones treated with CBZ and T3+BS significantly reduced the percent of dead plant by 46.43%, 17.86% and 60.71%, respectively as compared to control (69.64%). At harvest stage, banana plant treated with CBZ+T3+BS gained the highest harvested yield in term weight of fruit bunch by 24.72 kg, followed by CBZ (18.3 kg) and T3+BS (17.87 kg), while the control plant without treated by any treatments gained the lowest weight by 9.45 kg. In conclusion, integration treatments of CBZ+T3+BS at 15DI is recommended to enhance growth and physio-biochemical responses in controlling Fusarium wilt disease, thus produce better yield of banana.